Ancient Civilisations of Anatolia and Historical Treasures of Turkey - Akşit, İlhan (1982)
7-73: Prehistoric Period. The Hattis. The Assyrian Trade Colonies. The Hittites. The Early Hittite State. The Hittite Empire. Life under the Hittites. Bo?azköy. Yaz?l?kaya. Alacahöyük. Hittite Rock Monuments. The Hieroglyphic Hittite Principalities. The U